Passive immunisation against respiratory syncytial virus: a cost-effectiveness analysis. Issue 7 (26th May 2010) - Rietveld, Edwin; Steyerberg, Ewout W; Polder, Johan J; Veeze, Henk J; Vergouwe, Yvonne; Huysman, Marianne WA; de Groot, Ronald; Moll, Henriëtte A
Abstract : Aim: The cost-effectiveness of passive immunisation against respiratory syncytial virus (RSV) in the Netherlands was studied by assessing incremental costs to prevent one hospitalisation in high-risk children using a novel individualised monthly approach. Methods: Cost-effectiveness analysis was performed by combining estimates of individual hospitalisation costs and monthly hospitalisation risks, with immunisation costs, parental costs and efficacy of passive immunisation for a reference case with the highest hospitalisation risks and costs of hospitalisation during the RSV season (male, gestational age ≤28 weeks, birth weight ≤2500 g, having bronchopulmonary dysplasia (BPD), aged 0 months at the beginning of the season (October)). Various sensitivity analyses and a cost-neutrality analysis were performed. Results: Cost-effectiveness of passive immunisation varied widely by child characteristics and seasonal month. For the reference case it was most cost effective in December at €13 190 per hospitalisation averted. Cost-effectiveness was most sensitive to changes in hospitalisation risk. For the reference case, cost neutrality was reached in December, if acquisition costs of passive immunisation decreased from €930 to €375, monthly hospitalisation risk increased from 7.6% to 17%, or hospitalisation costs increased from €10 250 to €23 250 per hospitalisation. Even if passive immunisation prevented all hospitalisations, costs per hospitalisation averted in December would still exceed €2645. Conclusions: Although cost-effectiveness of passive immunisation varied strongly by child characteristics and seasonal month, incremental costs per hospitalisation averted were always high. A restrictive immunisation policy only immunising children with BPD in high-risk months is therefore recommended. The costs of passive immunisation would have to be considerably reduced to achieve cost-effectiveness.